The Differences of Learning Motivation Between First Year Medical Students Who Live with Their Parents and Boarding House at Faculty of Medicine Sebelas Maret University - Deneisha Kartika Puspitarini; Murkati .; Sumardiyono . (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: Success in learning determined by many factors, one of them is family environment. First year medical students which mostly came from various area out of town experienced social transition and begin to live away from their families. This research aims to see the differences of learning motivation between first year medical students who live with their parents and boarding house at Faculty of Medicine Sebelas Maret University. This research also see block examination score as the outcome of learning motivation. Methods : This research was an obsercational analyticstudy with cross sectional design. It was done at Faculty of Medicine Sebelas Maret University. Samples were under 21 years old medical student of batch 2014 who chose medical major based on their willingness and not living with their family besides their parents. Sampling was done by purposive sampling method after selected based on inclusion and exclusion criteria. The independent variable is residency while the dependent variable is learning motivation. Research subject completed (1) informed consent, (2) academic motivation scale questionnaire, (3) bio data and residency questionnaire. The secondary data is block examination score. Data obtained were 100 research subjects and analyzed using t-test Result : Statistical analysis shows significant relationship of learning motivation first year medical students who live with their parents and boarding house (p= 0,001). This research analysis also show significant relationship between learning motivation and block examination score (p = 0,005) Conclusion : Statistically, there is a significant difference that students who live with their parents have higher learning motivation than students in boarding house at Faculty of Medicine Sebelas Maret University. Keywords : residency, learning motivation, block examination score